1989
DOI: 10.1258/002367789780810608
|View full text |Cite
|
Sign up to set email alerts
|

Cage design reduces emotionality in mice

Abstract: SummaryTo see if a more natural cage design would alter the reactivity of laboratory mice, 192 mice were reared in cages with (1) no dividers, (2) five vertical dividers, (3) nine vertical dividers, or (4) nine vertical dividers and one horizontal platform. The mice preferred the most complex cages, and on almost all measures they were less emotional when reared in the more complex cages. Results suggest that a more natural housing environment would lead to healthier animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 3 publications
2
48
0
2
Order By: Relevance
“…However, Chamove (1989) looked at several measures of mouse behaviour and emotionality as well as weight gain and adrenal weight in cages of four different designs. In his experiments, weight gain correlated closely with cage preferences, activity, and lack of emotionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Chamove (1989) looked at several measures of mouse behaviour and emotionality as well as weight gain and adrenal weight in cages of four different designs. In his experiments, weight gain correlated closely with cage preferences, activity, and lack of emotionality.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be necessary to discover whether this is a real and repeatable effect. Similarly, in view of the work of Chamove (1989) and White et al (1989), it may well be worth discovering whether further development of the concept of cage accessories which break up the total cage space is worth pursuing. In these experiments the effects of the accessories were slight, and any significant effects were generally adverse, but possibly the design of such accessories is critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown a wide range of positive effects to enriching laboratory rats' environment including behavioural (Kaliste et al, 2006;Zaias et al, 2008;Abou-Ismail et al, 2010;Lidfors et al, 2014), physiological (Eckert et al, 2010;Azar et al, 2012;Sharp et al, 2014), psychological (Chamove, 1989b;Patterson-Kane et al, 1999), developmental (Mirmiran et al, 1982;Kempermann et al, 1997;van Praag et al, 2000), therapeutic and recovery from neural deficits (Jenks et al, 2013;Darwish et al, 2014;Greifzu et al, 2014) cognitive ability and memory, (Harris et al, 2008;Lyst et al, 2012;Jenks et al, 2013) and physical growth and functions and development of the brain (Nithianantharajah and Hannan, 2006;de Carvalho et al, 2010;Eckert et al, 2010;Skillings et al, 2014). Moreover, it has been shown that animals exposed to human and environmental enrichment (novel objects) early in life were easier to handle, less sensitive to novel situations they experience in later life, easier to catch (Csatádi et al, 2005;Moons et al, 2004), and displayed some improved parameters of wellbeing and various stress responses (Belz et al, 2003;Cloutier et al, 2013;Del Arco et al, 2007;Klein et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, another aspect of the cage, its material structure, has received less attention. evidence has suggested that laboratory rodents prefer, or have better production records in, opaque cages compared with transparent ones [5], polypropylene cages compared with wire ones [16], elongated cages compared with square ones [5,41], and divided cages compared with undivided ones [11]. one characteristic of the cage material that has not been investigated is color.…”
Section: Introductionmentioning
confidence: 99%